2020
DOI: 10.22374/jspv.v2i1.5
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cardinal Gaze Speed between Major League Baseball Players, Amateur Prospects, and Non-athletes

Abstract: PurposeSensorimotor variables have been shown to predict performance in professional baseball players. However, cardinal gaze speed in baseball players has received only limited attention. This study tested the hypothesis that the cardinal gaze speed in Major League Baseball (MLB) players would be faster than in amateur prospects and non-athletes. MethodSeventeen MLB athletes, 160 amateur prospects, and 128 non-athletes were tested using an eye-tracking test (i.e., the RightEye CGP test) designed to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…[62][63][64][65] A study comparing saccade speeds into cardinal gaze positions using RightEye (RightEye LLC, Bethesda, MD) measurements found the professional baseball players had significantly faster speeds in several directions when compared with amateur prospects and nonathletes. 66 Similar differences in head movement have been noted with tennis strokes between experienced and inexperienced players. 67 Positive positional errors are created by displacing the saccadic target in the same direction as the saccadic movement after initiation of the saccade.…”
Section: Static Visual Acuitysupporting
confidence: 52%
See 1 more Smart Citation
“…[62][63][64][65] A study comparing saccade speeds into cardinal gaze positions using RightEye (RightEye LLC, Bethesda, MD) measurements found the professional baseball players had significantly faster speeds in several directions when compared with amateur prospects and nonathletes. 66 Similar differences in head movement have been noted with tennis strokes between experienced and inexperienced players. 67 Positive positional errors are created by displacing the saccadic target in the same direction as the saccadic movement after initiation of the saccade.…”
Section: Static Visual Acuitysupporting
confidence: 52%
“…Studies with college and professional baseball players found similar head tracking of pitches from a ball machine or live pitcher that assists the maintenance of gaze position close to the ball 62–65 . A study comparing saccade speeds into cardinal gaze positions using RightEye (RightEye LLC, Bethesda, MD) measurements found the professional baseball players had significantly faster speeds in several directions when compared with amateur prospects and nonathletes 66 . Similar differences in head movement have been noted with tennis strokes between experienced and inexperienced players 67 .…”
Section: Perceptual Mechanism Assessmentsmentioning
confidence: 99%
“…Eyetracking skills are noticeably better in the Major League Baseball players, demonstrated by general oculomotor speed being a significant predictor of league level in baseball (Liu et al, 2020a). Research has also shown significant differences in other eyetracking abilities, including cardinal gaze between professional baseball players versus amateurs and non-athletes (Kubitz et al, 2020). Furthermore, there are several recent reviews of visualmotor control in baseball.…”
Section: Introductionmentioning
confidence: 99%